Income and Separation - Norris, K; Bradbury, B (My University, 2005)
What factors are associated with marital separation? In particular, is there a ‘social class gradient’ for separation? This article addresses these questions using data from two large Australian longitudinal data sets. The main focus is on the association between income support status/family income and the probability of separation. We find that recipients of income support from government are more than twice as likely to separate as non-recipients of income support. De facto couples are more likely to separate than legally married couples, though separation rates within the de facto married population have more variation with income than among legally married couples. The relationship between separation and demographic and health characteristics is also explored and we find that couples where the husband has depressive symptoms are more likely to separate. The article concludes by discussing the potential explanations for the association between income and separation.
Journal of Sociology
Keywords: Finance -- Income (Salary and Wages); Finance; Income, wealth and finances; Finance; Income (Salary and Wages); Income, wealth and finances